Analisis Perlindungan Hukum terhadap Nasabah Manipulasi Kredit oleh Karyawan Perbankan - Sri Andrian; Munawir; T. Rasyidin; Juanda (LP3M Sekolah Tinggi Ilmu Hukum Al-Banna, 2025)
Fraud in banking often occurs through credit manipulation, including fictitious loans or fictitious collateral using customers’ documents, even after previous loans have been settled. Such practices undermine the trust principle that underpins the bank–customer relationship as reflected in Article 29(4) of Law No. 10 of 1998, which requires banks to conduct their business in ways that do not harm the bank or customers’ interests and to maintain public trust. This study examines the urgency of the trust principle in banking and analyzes legal protection for customers harmed by credit manipulation committed by bank employees. The research employs an empirical juridical approach, combining normative analysis of relevant banking and civil law rules with field-based data on how credit manipulation is carried out and addressed in practice. The findings show that customer protection should be structured through preventive measures (internal controls, verification, complaint-handling mechanisms) and repressive measures (dispute resolution and law enforcement) across civil, criminal, and administrative avenues. From a civil law perspective, Articles 1365 and 1367 of the Civil Code provide the basis for holding both the employee and the bank institutionally liable for unlawful acts and vicarious responsibility, including compensation for customers whose identities or credit files are misused. Nevertheless, the quantification of damages remains case-specific and depends on proven material and immaterial losses.